2008
DOI: 10.1016/j.ejcts.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Is routine chest X-ray following mediastinal drain removal after cardiac surgery useful?

Abstract: Incidence of pneumothorax following mediastinal drain removal is very low. Clinical signs and symptoms almost always identify those few patients requiring intervention and the decision to obtain an X-ray could be based on clinical judgement alone. In addition, this approach may result in cost savings without compromising patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 7 publications
1
34
1
Order By: Relevance
“…In the present study, as opposed to hypertension that had no relationship with postoperative atelectasis, there was a significant relationship between hyperlipidemia and postoperative atelectasis (p≤0.000) because 44.1% out of 60 patients with diabetes and 40% out of 82 patients with hyperlipidemia faced with postoperative atelectasis. This finding is in line with that of the study conducted by Tanveer et al ( Khan et al, 2008 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, as opposed to hypertension that had no relationship with postoperative atelectasis, there was a significant relationship between hyperlipidemia and postoperative atelectasis (p≤0.000) because 44.1% out of 60 patients with diabetes and 40% out of 82 patients with hyperlipidemia faced with postoperative atelectasis. This finding is in line with that of the study conducted by Tanveer et al ( Khan et al, 2008 ).…”
Section: Discussionsupporting
confidence: 94%
“…Where these lines were observed in different parts of lung and they were not specific to a single part, the atelectasis was linear. When the lines were limited to the fissures between the lung lobes and did not cause the fissures to move, it was called segmental atelectasis, and if the lines caused the fissures to move toward mediastinum, heart, and endotracheal tube, it was considered as lobar atelectasis ( Khan et al, 2008 ). The collected data were fed to SPSS 16.0.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] The diagnostic and therapeutic efficacy of all these routine CXRs has been reported to be low. [1][2][3][6][7][8][9]11,13,14,[16][17][18][19]21 Investigators comparing a routine CXR strategy with an on-demand CXR strategy were not able to show any difference in outcome measures. [22][23][24][25][26][27][28] Although those studies indicated that a more restrictive CXR strategy should be safe, a more recent meta-analysis by Ganapathy and colleagues 26 stated that, in those studies, the confidence intervals were wide, and the study populations were small.…”
Section: See Editorial Commentary Page 230mentioning
confidence: 99%
“…Multiple investigators have studied the clinical value of routine CXRs after central venous catheterization, endotracheal intubation, and chest tube placement or removal. [1][2][3][4][5][6][7][8][9][10][11][12] Others have studied the value of daily routine CXRs in a mixed ICU population, or in mechanically ventilated patients only. [13][14][15][16][17][18][19][20][21] The diagnostic and therapeutic efficacy of all these routine CXRs has been reported to be low.…”
Section: See Editorial Commentary Page 230mentioning
confidence: 99%
“…Multiple investigators have studied the clinical value of routine CXRs following central venous catheterization, endotracheal intubation and chest tube placement or removal [ 1 ]-[ 12 ]. Others have studied the value of daily routine CXRs in a mixed ICU population or in mechanically ventilated patients only [ 13 ]-[ 22 ] The diagnostic and therapeutic efficacy of these routine CXRs is known to be low [ 1 ]-[ 3 ],[ 6 ]-[ 9 ],[ 11 ],[ 13 ],[ 14 ],[ 16 ]-[ 19 ],[ 22 ]. Investigators comparing a routine CXR strategy with an on-demand CXR strategy were not able to show any difference in outcome measures [ 23 ]-[ 29 ], but a more recent meta-analysis by Ganapathy et al indicated that study populations were small and that eventually missed findings in a restrictive strategy were not evaluated frequently enough [ 27 ].…”
Section: Introductionmentioning
confidence: 99%